1998
DOI: 10.1080/140174398427956
|View full text |Cite
|
Sign up to set email alerts
|

Release and effects of calcitonin gene-related peptide in myocardial ischaemia

Abstract: Scand Cardiovasc J Downloaded from informahealthcare.com by SUNY State University of New York at Stony Brook on 11/01/14 For personal use only. Release and effects of calcitonin gene-related peptide in myocardial ischaemia 2 Scand Cardiovasc J Downloaded from informahealthcare.com by SUNY State University of New York at Stony Brook on 11/01/14 For personal use only.Capsaicin also has positive chrono-and inotropic properties in vitro in many species (Lundberg et al., 1984), but the Göran Källner 5 Scand Cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 170 publications
(227 reference statements)
0
4
0
Order By: Relevance
“…The α-and β-CGRP isoforms are encoded in different genes and differ from each other in rats or humans in only one or three amino acids (Kallner 1998). Both α-and β-CGRP are synthesized in the cell bodies of primary sensory neurons and transported axonally mainly to peripheral, but also to central nerve terminals, where they are stored in large, dense-cored secretory granules (Kallner 257 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The α-and β-CGRP isoforms are encoded in different genes and differ from each other in rats or humans in only one or three amino acids (Kallner 1998). Both α-and β-CGRP are synthesized in the cell bodies of primary sensory neurons and transported axonally mainly to peripheral, but also to central nerve terminals, where they are stored in large, dense-cored secretory granules (Kallner 257 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is released from the heart in laboratory species in response to ischemia and low pH (105), with evidence that endothelium-derived prostacyclin (PGI 2 ) may also play a role in CGRP release (178). Infusion of CGRP was shown to attenuate and delay ischemia reperfusion arrythmias in the anesthetized rat (397), and these beneficial effects have been shown to be inhibited by CGRP 8 -37 in vitro (222).…”
Section: A Cgrp: a Protective Factor?mentioning
confidence: 97%
“…Upon activation of Cfibres during ischaemia, orthodromic impulses mediate the perception of pain, whereas antidromic impulses elicit CGRP release from the peripheral nerve endings (Jancsó et al 1977). The significance of the release of sensory neuropeptides from the stimulated sensory nerve terminals has been confirmed by the detection of these peptides at the site of preconditioning (Källner 1998;Brzozowski et al 2004) and in the bloodstream (Chai et al 2006), which is presumed to contribute to the transduction of precondition- Fig. 5 Changes in secondary leukocyte-endothelial cell interactions (sticking) in postcapillary venules of the tibial periosteum in rats subjected to a 60-min ischaemia followed by 180 min of reperfusion (IR); to IPC+IR (two cycles of 10 min of complete limb ischaemia and 10 min of reperfusion before IR); to hCGRP administration (0.3 μg kg −1 , i.v., prior to ischaemia); to RTX pretreatment (3× 15 μg kg −1 , s.c., 2 weeks before IR); or to CGRP 8-37 treatment (30 μg kg −1 h −1 , i.v., during the reperfusion period).…”
Section: Discussionmentioning
confidence: 92%
“…substance P and neurokinin A (Maggi 1995). CGRP and substance P released have already been addressed as mediators of preconditioning in animal (Ferdinandy et al 1997;Wang and Wang 2005) and human tissues (Källner 1998;Brzozowski et al 2004). It has been shown that substance P-mediated vasodilation is diminished after heart IR and restored by IPC (Chlopicki et al 1999).…”
Section: Discussionmentioning
confidence: 97%